A simple cobalt-based catalyst system for the controlled dehydropolymerisation of H3B·NMeH2 on the gram-scale. Issue 3 (12th December 2019) - Boyd, Timothy M.; Andrea, Kori A.; Baston, Katherine; Johnson, Alice; Ryan, David E.; Weller, Andrew S.
Abstract : A simple Co-based catalyst system promotes the efficient and controlled dehydropolymerisation of amine–boranes on scale. Abstract : A simple Co(ii )-based amine–borane dehydropolymerisation catalyst system is reported that operates at low loadings, to selectively give (H2 BNMeH) n polymer on scale, with catalyst control over M n, narrow dispersities and low residual metal content.